Lexical and Grammatical Aspect of Studying Russian Prefixal Verbs - Elena P Krasilnikova (RUDN Journal of Language Studies, Semiotics and Semantics, 2016)
This article focuses on the types of exercises and textual materials used for the foreign students in the study of prefixal verbs of the Russian language, provides the algorithm of theoretical and practical materials on the topic. The article gives examples of using different kinds of texts in the aspect of functional and genre interrelationship: humorous mini-texts, educational texts, the texts online culturological content resources, articles of online dictionaries, electronic resources of the Russian National Corpus and other materials. Suggested types of tasks demonstrate the practice of innovative learning technologies, apply principles of clarity, gradual development of knowledge and contribute to the formation of communicative competence of the learners.